P1-S5.44 STD rates in the eight Americas: "Disparities in the burden of syphilis, gonorrhoea, and chlamydia across race and county". (10th July 2011) - Chesson, H; Owusu-Edusei, K; Kent, C; Aral, S
Abstract : Background: The purpose of this study was to examine rates of three STDs (primary and secondary syphilis, gonorrhoea, and chlamydia) in eight subpopulations (known as the eight Americas) defined by a small number of sociodemographic and geographical characteristics. Methods: A list of the race-county combinations comprising each of the eight Americas was obtained from the corresponding author of the original eight Americas project, which examined disparities in mortality rates across the eight Americas. Using county-level STD surveillance data, we calculated syphilis, gonorrhoea, and chlamydia rates (new cases per 100 000) for each of the eight Americas. Results: STD rates varied substantially across the eight Americas. STD rates were generally lowest in America 1 (Asian and Pacific Islanders in selected counties) and America 2 (Northland low-income rural white) and highest in America 6 (Black Middle America), America 7 (Southern low-income rural black), and America 8 (High-risk urban black) see Abstract P1-S5.44 Table 1 . Conclusions: The disparities in STD rates we observed across the eight Americas were akin to the disparities in mortality rates and life expectancy reported by the authors of the original eight Americas study. Although disparities in STDs across the eight Americas are generally similar to the well-established disparities in STDs across race/ethnicity, the grouping of US race-counties into the eight Americas does offer additional insight into disparities in STDs in the USA. The high STD rates we found for Black Middle America relative to Middle America are consistent with the assertion that sexual networks and social factors are more important drivers of racial disparities in STDs than differences in sexual behaviours.